A Case Study of Consumer Satisfaction That Leads to Loyalty towards McDonald’s - Shasha Eisyami; Siti Nadiah; Siti Zahrah; Sim Chee Kee; Ishika Singhal (AIBPM Publisher, 2022)
The purpose of this study is to review the satisfaction of consumers in McDonald's (the foodservice industry) that leads to loyalty to the brand. It also reviews how McDonald's reacts to changes in the environment and consumer behavior. McDonald's has a strong ambition of providing the best fast service eating experience in the global fast-food market as a world fast-food enterprise. Being the best implies providing exceptional value in both quantity and quality of the product and services, ensuring that every customer is delighted with the brand. In addition, McDonald's believes that job happiness and motivation are some of the biggest influences on consumer satisfaction. The study is organized by collecting the data from consumers through a self-administered questionnaire survey and was distributed to 100 respondents. The results show that for overall satisfaction, most respondents slightly agree that McDonald's has given great services to satisfy their customer needs.Â Keywords: Consumer Satisfaction, McDonaldâ€™s, Foodservice, Marketing Research